Decision Support System For Supplementary Food Recipients (PMT) By Using The Simple Additive Weighting (SAW) Method - Maulisa Puspa (Institute of Computer Science (IOCS), 2019)
Additional Food Recipients (PMT) is a program that is held in every village, especially in the Kubah Sentang Village, which is budgeted annually by the Village Officials through the APBN Fund. The importance of PMT for this Kubah Sentang village is because the poverty rate is quite high reaching 65% and the nutritional intake obtained is very limited especially for toddlers aged 6-59 months. This has led to the need to build a system that can facilitate government agencies, especially in the Kubah Sentang Village Office to select additional food recipients using a Decision Support System with the Simple Additive Weighting (SAW) method. Decision support systems are very necessary in government agencies, especially in the Kubah Sentang Village Office to select recipients of supplementary food (PMT) for the community. The determination of the criteria for additional food recipients is determined from the age of the baby, nutritional status, income of parents, and class of electric power. This study also produced a system that was able to display recommendations for prospective supplementary food recipients with the results of criteria and preference weights that were determined by the system's needs.